PENGARUH EKUITAS MEREK TERHADAP NIAT BELI DENGAN NORMA SUBYEKTIF SEBAGAI PEMODERASI (STUDI PADA KONSUMEN NOTEBOOK MEREK ASUS DI KOTA BANDA ACEH) - Maulita Sari, Jeliteng Pribadi (Departemen Manajemen, 2018)
This research aims to know the effect of brand equity to purchase intention with subjective norms as a moderating. The empirical study conducted at Asus brand notebook consumers in Banda Aceh City, used a questionnaire as research instrument, which sample in this study of 150 people. Non Probability Sampling is used as sampling technique with Purposive Sampling method. The analysis method is Moderated Regression Analysis (MRA) is used as the method of analysis with IBM SPSS 20 software. The result of this research indicates that the brand equity influential purchase intention, subjective norm influential on purchase intention, and beside that result that subjective norm moderate influential of brand equity to purchase intention.Keywords: Brand Equity, Subjective Norms, and purchase intention